Control of Deep Currents on Sediment and Cold-Water Coral Distribution on the Northern Manihiki Plateau - Bashah, Sara; Galvez, Kimberly C.; Eberli, Gregor P.; Cantwell, Kasey (Frontiers in Marine Science, 2020)
High-definition video surveys of remotely operated vehicle (ROV) dives from the NOAA’s Mountains in the Deep 2017 expedition (EX1705) cruise along volcanic ridges and seamounts of the Manihiki Plateau coupled with multibeam bathymetry data and water column profiles, reveal no or minimal sediment cover on the basaltic edifice, but variable amounts of cold-water corals on ferromanganese-encrusted basaltic rocks. Coarse sediment, however, accumulates in crevasses and sedimentary ripples testify the existence of currents in the area. Collectively, these observations illustrate the strong influence of deep currents on the surficial geology and cold-water coral distribution at ~2,000 m water depths. Dive transects along two basaltic seamounts show stark differences of sedimentary features and cold-water coral distribution. On the ridges of “Te Kawhiti” (water depth: 2,089-2,220 m), basaltic slabs, and cold-water corals are far more abundant in comparison to the slope of a mesa in “Te Tuku” (water depth: 2,440-2,495 m). The increased abundance on “Te Kawhiti” is due to the exposure of “Te Kawhiti” to Lower Circumpolar Deep Water that sweeps the summit of the ridges as indicated by frequent ripples observed in between the basaltic rocks. The currents are strong enough to sweep fine-grained sediments away, leaving coarse-grained sediments behind, inducing the formation of ferromanganese crust on the basaltic rocks. Both dive sites are below the high-Mg calcite saturation horizon, and as a result, the cold-water coral community is dominated by Isididae, which can build a high-Mg calcite skeleton in water undersaturated in regards to high-Mg calcite